THE FALLACY OF PERSONAL VALIDATION (THE FORER EFFECT) IN THE SYSTEM OF BEHAVIORAL FINANCE BIASES - Hayrapetyan , D.R. (Modern Psychology, 2022)
The main purpose of the research paper is to understand the interrelation of the fallacy of personal validation also called The Forer effect or The Barnum effect with one of the main biases of behavioral finances – the money illusion. During the last years we explored some personal factors which force and determinate the manifestation of money behavior such as subjective control, aspiration level etc. All of data force us to suppose that one of regulators of money behaviour is the belief in authority and obedience to expert opinion which could be measured by the level of manifestation of the fallacy of personal validation. This means that people are gullible because they think the information is about them only when in fact the information is generic. The research design is aimed to study and understand the manifestation of the money illusion among the people affected by the fallacy of personal validation (The Forer effect). This can help us to understand more deeply the phenomena of money illusion which nowadays affect more extensively our financial behaviour.